2015
DOI: 10.1371/journal.pone.0135661
|View full text |Cite
|
Sign up to set email alerts
|

Aphid Parasitoid Mothers Don't Always Know Best through the Whole Host Selection Process

Abstract: Parasitoid host selection behaviour has been extensively studied in experimentally simplified tritrophic systems formed by one single food chain (one plant, one herbivore and one parasitoid species). The "Mother knows best" hypothesis predicts that the preference for a plant-host complex should be positively correlated with plant quality for offspring performance. We studied the host selection behaviour of the generalist endoparasitoid Aphidius matricariae towards the black bean aphid Aphis fabae in the interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…A specific component of the biotic environment is the quality of the plant and aphid species forming the parasitoid wasp maternal environment, which can alter the offspring’s oviposition choice. For example, Chesnais et al [15] tested how changing the host plant species of black bean aphids ( Aphis fabae ) influenced oviposition by a parasitoid wasp ( Aphidius matricariae ). They showed that mother parasitoid wasps were more attracted to the plant host environment that produced offspring with the lowest fitness, but oviposition frequency was highest on the plant species that resulted in the fittest offspring [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A specific component of the biotic environment is the quality of the plant and aphid species forming the parasitoid wasp maternal environment, which can alter the offspring’s oviposition choice. For example, Chesnais et al [15] tested how changing the host plant species of black bean aphids ( Aphis fabae ) influenced oviposition by a parasitoid wasp ( Aphidius matricariae ). They showed that mother parasitoid wasps were more attracted to the plant host environment that produced offspring with the lowest fitness, but oviposition frequency was highest on the plant species that resulted in the fittest offspring [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chesnais et al [15] tested how changing the host plant species of black bean aphids ( Aphis fabae ) influenced oviposition by a parasitoid wasp ( Aphidius matricariae ). They showed that mother parasitoid wasps were more attracted to the plant host environment that produced offspring with the lowest fitness, but oviposition frequency was highest on the plant species that resulted in the fittest offspring [15]. Although maternal effects were not tested specifically in the latter study, they have potential to influence the regulation of aphid populations [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Although oviposition in soybean‐fed hosts appears to be the optimal choice due to higher survival rates of host larvae (Nadgauda & Pitre, ), herbivore‐related experience (with cotton‐fed hosts) may override such considerations. This contradicts the “mother knows best” hypothesis (Henry et al ., ; Chesnais et al ., ). In fact, preference‐performance hypothesis may not adequately explain host selection; possible conflicts between the needs of progeny and behavioral dynamics of mother insects should also be considered (Scheirs & De Bruyn, ; McCormick et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Parasitoids share an intimate life history with their hosts. According to the optimal foraging theory, female parasitoids are expected to select hosts that best support the development of their progeny (Pyke, ; Goubault et al ., ; Steiner et al ., ; Chesnais et al ., ). Parasitoid species that are not time‐limited are expected to discriminate hosts based on suitability and quality (Hopper et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The optimal foraging theory predicts that a foraging female parasitoid will always prefer the most profitable host [ 25 ]. This is in relation to the preference-performance hypothesis (PPH), also known as the “mother knows best” hypothesis [ 26 ], which states that host preference in female parasitoids is positively correlated to the developmental success of its progeny [ 27 , 28 , 29 , 30 , 31 ]. However, in some cases, female inexperience or defensive behaviours of the host which can decrease its profitability by increasing the handling time [ 32 ] for example, it can lead to choices that can seem suboptimal [ 33 ].…”
Section: Introductionmentioning
confidence: 99%